1988
DOI: 10.1007/bf00640665
|View full text |Cite
|
Sign up to set email alerts
|

The danger of an inadequate water intake during prolonged exercise

Abstract: To prevent thermal injuries during distance running, the American College of Sports Medicine proposes that between 0.83 and 1.65 l of water should be ingested each hour during prolonged exercise. Yet such high rates of fluid intake have been reported to cause water intoxication. To establish the freely-chosen rates of fluid intake during prolonged competitive exercise, we measured fluid intake during, body weight before and after, and rectal temperature after competition in a total of 102 runners and 91 canoei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
2

Year Published

1990
1990
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(58 citation statements)
references
References 29 publications
5
50
0
2
Order By: Relevance
“…In a review, on the fluid replacement of athletes Casa and colleagues (2000) reported that dehydration of 1-2% body weight increases physiological stress and decreases performance. However, in reality, it is often difficult and sometimes impossible to prevent at least some dehydration during repeated heat stress (Convertino et al 1996) and this has been considered of little consequence by some authors (Noakes et al 1988;Greenleaf 1991), on the basis that this readily occurs during repeated heat exposure. In summary, we postulate that the increased physiological strain of restricted fluid replenishment during DEH acclimation may have resulted in adaptation of the fluid-regulatory system.…”
Section: Fluid Regulation and Blood Volume Response To Repeated Heat mentioning
confidence: 99%
See 1 more Smart Citation
“…In a review, on the fluid replacement of athletes Casa and colleagues (2000) reported that dehydration of 1-2% body weight increases physiological stress and decreases performance. However, in reality, it is often difficult and sometimes impossible to prevent at least some dehydration during repeated heat stress (Convertino et al 1996) and this has been considered of little consequence by some authors (Noakes et al 1988;Greenleaf 1991), on the basis that this readily occurs during repeated heat exposure. In summary, we postulate that the increased physiological strain of restricted fluid replenishment during DEH acclimation may have resulted in adaptation of the fluid-regulatory system.…”
Section: Fluid Regulation and Blood Volume Response To Repeated Heat mentioning
confidence: 99%
“…The use of permissive dehydration during acclimation contradicts the existing fluid replenishment guidelines for heat acclimation, which recommend the maintenance of good hydration status during exposure to heat stress conditions (Armstrong and Maresh 1991;Convertino et al 1996;Cheung and McLellan 1998;Casa et al 2000). However, the reality for many people undergoing acclimation bouts is that some level of dehydration is normal, if not frequently inevitable (Noakes et al 1988;Greenleaf 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the relatively severe dehydration induced by the marathon in this study (5.5% weight loss), core temperature was maintained within expected range (36.6 -38.9 CC). This is consistent with previous studies (Pugh et al 1967;Maughan et al 1985;Myhre et al 1985;Noakes et al 1988). The rise in core temperature is directly related to the metabolic rate and thus running speed sustained during prolonged exercise (Maughan et al 1985;Noakes et al 1991a).…”
Section: Discussionsupporting
confidence: 94%
“…On the other hand, it has been proposed that the rate of fluid intake should be less than the rate of sweat loss due to the fact that metabolic water and water stored with glycogen is released during exercise, and thus should not be taken into account when estimating the rate of fluid intake. On that basis, it has been recommended that an average fluid intake of 0.5 l.h-l is an adequate rate of fluid replacement during prolonged exercise (Noakes et al 1988). This rate of fluid intake appears to be the ad libitum fluid intake during prolonged exercise such as marathon running.…”
Section: Influence Of Dehydration and Fluid Ingestion On Temperature mentioning
confidence: 99%
“…Before 1981, athletes were encouraged to drink heavily during exertion to avoid dehydration (7,31). With the description of EAH in South Africa and New Zealand in 1985, new fluid consumption guidelines that restricted overzealous fluid intake for endurance events in these countries were promoted (32,33). Concomitant with these recommendations, the incidence of EAH fell in both of these regions (19,20).…”
Section: Risk Factorsmentioning
confidence: 99%